2009
DOI: 10.3198/jpr2008.12.0715crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Willow Creek’ Forage Wheat

Abstract: ‘Willow Creek’ forage winter wheat (Triticum aestivum L.) (Reg. No. CV‐1032, PI 655073) was released by the Montana Agricultural Experiment Station. Awnletted cereal forages are widely used for hay production on integrated crop–livestock operations in the Northern Great Plains. Five awnletted winter wheat accessions were evaluated for forage characteristics in 1996 and 1997, and Willow Creek was selected directly from PI 306505. Willow Creek was evaluated in replicated trials for forage yield and quality, grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
14
1
Order By: Relevance
“…Total forage DM yield of triticale selections in the current study are similar to reported yields of 4.7 to 7.9 Mg/ha in drier environments in the CHP region (9). Dry matter yield of Willow creek (forage winter wheat released by Montana State University) in this study was lower than those reported for Montana and eastern Wyoming (3). Seasonal total DM yield of Willow creek ranged from 2.9 to 5.1 Mg/ha, lower than DM yield of other small grains evaluated in this study.…”
Section: Forage Dry Matter Yieldcontrasting
confidence: 86%
See 1 more Smart Citation
“…Total forage DM yield of triticale selections in the current study are similar to reported yields of 4.7 to 7.9 Mg/ha in drier environments in the CHP region (9). Dry matter yield of Willow creek (forage winter wheat released by Montana State University) in this study was lower than those reported for Montana and eastern Wyoming (3). Seasonal total DM yield of Willow creek ranged from 2.9 to 5.1 Mg/ha, lower than DM yield of other small grains evaluated in this study.…”
Section: Forage Dry Matter Yieldcontrasting
confidence: 86%
“…Therefore, protein supplementation may be required to improve animal intake and performance (6). Small grain forages have potential for beef cattle production in the CHP and other western mountain states (3,13). There is limited information on seasonal forage productivity and nutritive value of small grains in the CHP region of Wyoming.…”
Section: Introductionmentioning
confidence: 99%
“…However, barley is planted in spring, as opposed to winter wheat planted in autumn. Recently, the Montana Agricultural Experiment Station released a winter wheat cultivar bred expressly for feeding cattle during the early-season period before barley becomes sufficiently mature [37].…”
Section: Indirect Land-use Changementioning
confidence: 99%
“…Subplots were three fall‐planted winter cereals and a single spring‐planted cereal. Fall‐seeded cereal entries were ‘Bobcat’ triticale (Salmon et al, 2000), and ‘Yellowstone’ (Bruckner et al ., 2007) and ‘Willow Creek’ (Cash et al ., 2009) winter wheat. Spring‐seeded ‘Hays’ barley was included as a spring‐planted control.…”
Section: Experimental Designmentioning
confidence: 99%